THE IMPACT OF ARTIFICIAL INTELLIGENCE ON NEUROLOGICAL DIAGNOSTICS AND TREATMENT - Anvarova Sevara Mirzoxid qizi; Ismanova Arofatxon Abduldulhamidovna (TADQIQOTLAR, 2025)
Abstract. Information technologies (IT) have transformed various aspects of healthcare, particularly in the field of neurology. The use of IT enhances diagnostic precision,  facilitates  remote  consultations,  and  optimizes  the  management  of neurological  diseases.  This  article  explores  the  revolutionary  role  that  AI  plays  in neurological  diagnostics  and  treatment.  We  will  examine  how  AI  is  being  used  to enhance diagnostic accuracy, the potential benefits it offers in personalized treatments, and the future directions of AI technologies in neurology. Through the exploration of case studies and the latest research, we will gain insight into how AI is shaping the future of neurological healthcare.